Discrete Weighted Pseudo Almost Automorphic Solutions of Nonautonomous Difference Equations - Xiaoqing Wen; Hongwei Yin (Discrete Dynamics in Nature and Society)
We introduce the concept of a discrete weighted pseudo almost automorphic function and prove some basic results. Further, we investigate the nonautonomous linear and semilinear difference equations and obtain the weighted pseudo almost automorphic solutions of both these kinds of difference equations, respectively. Our results generalize the ones by Lizama and Mesquita (2013).